Potential output and output gap estimation models for the Philippines. - Mendoza, Adrian R.
Reliable estimates of the economyâ??s potential output and output gap are particularly important for inflation targeting and monetary policy setting in the Philippines. This paper examines alternative modeling approaches that can be used to estimate potential output and the output gap in the Philippines. Variations of statistically-based filtering methods, production function approach, and broad-based macroeconomic modeling approach are used to generate estimates of potential output for the Philippines. A contribution of this study in the empirical literature in the Philippines is the introduction of more comprehensive labor market and financial market conditions indices as explicit drivers of potential output. Given competing models for estimating the output gap, the paper also investigates the use of output gap estimates in forecasting inflation. The study also looks into the measurement of total factor productivity in the Philippines using production functions.